Comprehensive assessment of microalgal-based treatment processes for dairy wastewater - Singh, Pooja; Mohanty, Satya Sundar; Mohanty, Kaustubha (Frontiers in Bioengineering and Biotechnology, 2024)
The dairy industry is becoming one of the biggest sectors within the global food industry, and these industries use almost 34% of the water. The amount of water used is governed by the production process and the technologies employed in the plants. Consequently, the dairy industries generate almost 0.2 to 10 liters of wastewater per liter of processed milk, which must be treated before being discharged into water bodies. The cultivation of microalgae in a mixotrophic regime using dairy wastewater enhances biomass growth, productivity, and the accumulation of value-added product. The generated biomass can be converted into biofuels, thus limiting the dependence on petroleum-based crude oil. To fulfill the algal biorefinery model, it is important to utilize every waste stream in a cascade loop. Additionally, the harvested water generated from algal biomass production can be recycled for further microalgal growth. Economic and sustainable wastewater management, along with proper reclamation of nutrients from dairy wastewater, is a promising approach to mitigate the problem of water scarcity. A bibliometric study revealing limited work on dairy wastewater treatment using microalgae for biofuel production. And, limited work is reported on the pretreatment of dairy wastewater via physicochemical methods before microalgal-based treatment. There are still significant gaps remains in large-scale cultivation processes. It is also crucial to discover robust strains that are highly compatible with the specific concentration of contaminants, as this will lead to increased yields and productivity for the targeted bio-product. Finally, research on reutilization of culture media in photobioreactor is necessary to augument the productivity of the entire process. Therefore, the incorporation of the microalgal biorefinery with the wastewater treatment concept has great potential for promoting ecological sustainability.